Professor Janusz Wójcik - GAMBIN, Barbara; NOWICKI, Andrzej (Archives of Acoustics, 2023)
Janusz Wójcik was born in the heart of Poland near Czarnolas in August 1957. He obtained an M.Sc. Eng. degree at the Warsaw University of Technology in 1983. From 1984 until the last days of his life, he worked at the Institute of Fundamental Technological Research Polish Academy of Sciences in Warsaw. He received his doctoral degree on the basis of the dissertation “Nonlinear EnvelopeWaves in The Vlasov-Maxwell Plasma” in 1990. In 2004, he was given a permanent position of IPPT PAN professor and a year later he was appointed Head of the Ultrasound Introscopy Laboratory at the Department of Ultrasound.